13 original Broadway cast recording - Brown, Jason Robert 1970- (Ghostlight Records, 2009)
Almost thirteen-year-old Evan Goldman learns what it means to be a man when his parents separate and he and his mother move from New York City to Appleton, Indiana, right before his bar mitzvah